The Relationship of Digital Literacy and Student Engagement on Student English Learning - Triana, Hilda; Suryadi (Institut Agama Islam Negeri Palopo, 2025)
This study examines the relationship between digital literacy and student engagement in English language learning among tenth-grade students at a rural Indonesian high school. Using a quantitative correlational approach, data were obtained from 100 students using a structured questionnaire (Cronbach’s α = 0.662). The analysis revealed a moderate, significant correlation between digital literacy and English learning achievement (r = 0.530), and a strong correlation between student engagement and achievement (r = 0.598). However, digital literacy was not significantly associated with engagement. These findings suggest that while digital skills contribute to achievement, they do not directly enhance engagement. This study applies the Self-Determination Theory framework and emphasizes the need for multifaceted strategies to foster engagement. Instrument reliability and contextual limitations are acknowledged. The findings offer insights for educators and policymakers in rural digital-based English instruction.